A Parthian port on the Persian Gulf: Characene and its trade - Gregoratti, Leonardo (Anabasis. Studia Classica et Orientalia, 2011)
Scholars have mainly focused their attention on the western connections of the south Mesopotamian kingdom of Characene, whose harbours appear in several texts of the well known caravan inscriptions from Palmyra. As a consequence this interesting and important state has been often regarded almost exclusively from a western point of view, which favoured the role it played as the main Palmyrenian trading partner in the East. The aim of this paper is to provide a different approach to this topic. The kingdom of Characene was part of the Arsacid empire and its historical role cannot be understood without taking into consideration also the history of the Parthian state and the relationship with its south Mesopotamian vassal kingdom. Parthian kings exploited the proficiencies the Characenians had gained in sea routes and trade rendering this small kingdom a sort of port for the entire Parthian empire. This can remind the role which another important ‘Port of the sands’, that is to say Palmyra, played for Rome, the Parthian neighbour. Apart from hosting Palmyra’s merchant colonies and within the Parthian state, Characene autonomously developed a trade network in the Persian Gulf, promoting the cultural evolution of the societies which belonged to its trade horizon.